(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The Buddhist concept of Nirvana, central to the teachings of the Buddha, represents liberation from the cycle of birth and death (samsara) and the cessation of suffering (dukkha). Originating in India in the 6th century BCE, this profound idea spread widely across Asia through trade, pilgrimage, monastic missions, and royal patronage. As Buddhism evolved, the interpretation of Nirvana diversified—ranging from the early Theravāda emphasis on individual liberation to Mahāyāna visions of universal salvation and Vajrayāna’s esoteric practices. This paper explores the historical, cultural, and philosophical trajectories of Nirvana’s transmission and transformation across South, Central, East, and Southeast Asia.